Marketing Mix Marketing Strategy Analysis in Increasing Cassava Chips Sales in Trading Businesses in Pangilen Village (Sampang District) - Moh Azfahani Zain; Abdur Rohman (Penerbit Hellow Pustaka, 2025)
The aim of the research is to determine the marketing strategy analysis for selling cassava chips to Pangilen village traders. This research method uses a qualitative approach with descriptive methods. Respondents to this survey were owners, employees, and customers. Interview, observation and documentary data collection techniques. Data analysis uses interactive analysis. Based on the research results, based on the discussion of the results of this research, the conclusion can be drawn that by using the Marketing Mix Strategy (4P), namely: 1. The product of the flour and cassava production business in Pangilen Village becomes a consumption ingredient, namely cassava chips snacks. The strategy used by the owner so that consumers are not disappointed is using quality raw materials, so that they do not damage the taste produced and in the processing it is also in accordance with the measurements so that the resulting taste is not bad or disappointing. There are factors that influence the increase in production of Cassava Chips in Pangilen Village when it has entered the rainy season 2. The price set by the owner, namely for cassava chips per pack, is Rp. 5,000.- To determine the selling price, of course the owner has taken into account the financing of raw materials, labor wages and the profits that will be obtained. With low prices and very affordable for all groups. 3. Promotion: Pak Heri's initial promotion to shops selling his own products. In the past, the owner only sold it little by little door to door and over time there were salespeople who came to take the cassava chips. Then there are flavors that are popular with many people, he innovated to make various types of cassava chips, such as: sweet spicy cassava chips, balado cassava chips, salted cassava chips, etc. 4. Place The place here plays an important role in increasing sales of Cassava Chips which we We have to analyze where is a strategic place to sell our products so that they can be known to many people, such as Mr Heri who opened a shop on Jl. Raya Pangilen, which is a very efficient place to market Cassava Chip products